Queue scheduling the Alan Cousins Telescope - Maartens, Deneys Sean (Department of Electrical Engineering, 2020)
The Alan Cousins Telescope is a 0.75-m automatic photoelectric telescope situated at the South African Astronomical Observatory, in Sutherland. The telescope was designed and built to execute a range of photometry programmes, but is used mainly for the long-term monitoring of variable stars. In addition, there is the potential for target-of-opportunity observations of unanticipated events, such as gamma ray bursts, and anticipated events such as occultations. Ultimately the telescope is intended to be a fully robotic telescope with limited operational support needs. Some advance toward this goal has been made by a full hardware interface to allow queue executions of observations. The next phase is the implementation of an automated scheduler that will generate a queue of valid observations for each night of observation. Queue scheduling algorithms are widely used in astronomy and the aim of this dissertation is to present a strawman scheduler that will generate the nightly observation queue. The main design of the scheduler is based on a merit-based system implemented at the STELLA robotic observatory, paired with the scheduling algorithms used by SOFIA. The main drawback of the telescope is that it does not currently accommodate dynamically changing weather conditions. As a consequence, the main scheduling constraints are observation parameters, instrument ability, and for monitoring type observations, observation time window constraints.